Para una teoría del arte en Historia y estilo de Jorge Mañach - Arencibia Coloma, Yaneidys (Book collections on Project MUSE., 2018)
For a theory of art in History and style exposes the contribution of Jorge Manach (1898-1961) to the theory of Cuban art, through the examination of History and style (1944), containing several fundamental texts, and through the use of concepts of analysis as "electivism, "long duration" and "theory of the historical circumstantiality of style", by virtue of specifying the method used by Manach, the historiographical conception that supports his proposal and the use of the essay as a textual support.